The hustler [videorecording (DVD)] - Newman, Paul, 1925-2008; Laurie, Piper, 1932-; Scott, George C., 1927-1999; Gleason, Jackie, 1916-1987; Tevis, Walter S. (Collector's edition (Twentieth Century Fox Home Entertainment, Inc.), 2007)
New York. Ames Billiards, with high ceilings and air of hushed concentration, is a church of pool. "Fast" Eddie Felson enters as an innocent con man and leaves with a taste of what the world can do, that talent alone will only get him so far, and that a man's search for "character," that hard-to-define quality that is simultaneously elusive and essential, could last a lifetime. Having come to take on pool legend Minnesota Fats, Eddie is soundly beaten because he doesn't know how to control his impulses. He finds comfort with down-and-out Sarah, a lonely part-time student with a drinking problem, and plans a comeback. Eddie makes a deal with Bert Gordon, a big-time gambler, to act as his manager and stake horse. Under Gordon's tutelage, Eddie learns hard lessons fast. In his rematch with Fats, Eddie wins a bittersweet victory, but can he regain his self-respect?